Modernisation of vocational education and training : the international consultancy adopted by BIBB - Schwarz, Michael [Verfasser]; Janssen, Bettina [Verfasser]; Caceres-Reebs, Diana [Verfasser]; Medrikat, Ilona [Verfasser] (Bundesinstitut für Berufsbildung, 2016)
"BIBB meets the challenge of the increasing globalisation, demographic change and developments in economy and technology by identifying future VET tasks, promoting innovations in national and international VET and developing practically oriented solutions for initial and continuing VET. As Germany's national and international centre of competence for VET, BIBB has been offering advice and support on the reform of the (vocational) education and training systems of other countries for many years." (Editor, BIBB-Doku)
Keywords: I 1.1 Systemberatung; Berufsbildung; Internationale Zusammenarbeit; Systemberatung [Berufsbildung]; Bundesinstitut für Berufsbildung